Optimised approach based on hybrid MAC protocol for M2M networks. Issue 6 (1st November 2018) - Saad, Waleed; El‐Feshawy, Somaya A.; Shokair, Mona; Dessouky, Mouad I.
Abstract : In machine‐to‐machine (M2M) networks, the ability to access the radio channel requires a rigid design of a medium access control (MAC) protocol. Here, an optimised hybrid MAC protocol will be proposed which is composed of two main processes, the contending process and the transmission process. During contention process, the devices randomly contend the transmission opportunities with equal probabilities by using the conventional‐based slotted ALOHA (S‐ALOHA) mechanism. Only successful devices can assign a transmission slot during the transmission process by using the reservation‐based time division multiple access mechanism. Additionally, an optimisation problem will be formulated to obtain the maximum aggregated throughput. Moreover, the optimum relation between the contention and transmission periods under different number of devices is calculated. The optimisation problem is solved with the aid of mathematical analysis which is carried out through Monte Carlo simulation. Furthermore, extensive MATLAB programs are executed to study the system performance in terms of: the system throughput, the average packet delay, the success access ratio, and the reservation ratio. The simulation results show that the proposed hybrid technique outperforms other related hybrid when compared.